2017
DOI: 10.2147/ijn.s134708
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of transdermal permeation promotion of lipophilic drugs by ethosomes

Abstract: Ethosomes can promote the penetration of lipophilic drugs into the skin, but the underlying mechanism is still unknown. The purpose of this study was to investigate the mechanism of transdermal permeation promotion of lipophilic drugs by ethosomes. The formulation of ethosomes was optimized using the Box–Behnken experimental design, in which Rhodamine B and 1-palmitoyl-2-{12-[(7-nitro-2-1,3-benzoxadiazol-4-yl)amino]dodecanoyl}- sn -glycero-3-phosphocholine were used to simulate a model l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 28 publications
0
59
0
1
Order By: Relevance
“…This renders the choice of a suitable fluorophore, with a distinct fluorescence from that of skin, not an easy option, especially due to the broad emission spectrum of skin. Even with suitable dyes, offsetting the skin's fluorescence was the solution used by different research groups for imaging of NPs in skin . However, the ability to image NPs together with skin structure will give visual evidence about the NP penetration within the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…This renders the choice of a suitable fluorophore, with a distinct fluorescence from that of skin, not an easy option, especially due to the broad emission spectrum of skin. Even with suitable dyes, offsetting the skin's fluorescence was the solution used by different research groups for imaging of NPs in skin . However, the ability to image NPs together with skin structure will give visual evidence about the NP penetration within the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Rh-B-loaded liposomes were applied to rat skin for permeation as described in above. Transverse sections of the treated area of skin were sliced using microtome (~10 µm thickness) to generate XZ-planar optical cross-sections and scanned under a confocal laser scanning microscope (Olympus IX 81 with FV 500) for fluorescence signals with an argon laser beam with excitation at 488 nm and emission at 560 nm for Rhodamine-B 28 . The depth of liposome penetration was calculated from the confocal images captured in the XY-plane of the sections (perpendicular to the plane of skin surface).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that propyl paraben is converted to several metabolites (Abbas et al, 2010;Bando, Mohri, Yamashita, Takakura, & Hashida, 1997;Jewell et al, 2007). It can be directly conjugated to form propyl paraben-sulfate and glucuronide; or conjugates can be formed after ester cleavage to 4-hydroxybenzoic acid.…”
Section: Esterase and Sulfotransferase/udp-glucuronyl Transferase Smentioning
confidence: 99%